2016
DOI: 10.1039/c6nr03199d
|View full text |Cite
|
Sign up to set email alerts
|

Protein patterning by a DNA origami framework

Abstract: A spatial arrangement of proteins provides structural and functional advantages in vast technological applications as well as fundamental research. Most protein patterning procedures employ complicated, time consuming and very costly nanofabrication techniques. As an alternative route, we developed a fully biomolecular self-assembly method using DNA Origami Frames (DOF) as a template for both small and large scale protein patterning. We employed a triangular DOF (tDOF) to arrange the Bovine Serum Albumin (BSA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…In addition, proteins may have a relatively weak interaction with our origami device because there is seldom empty space available for protein filling. For example, the study reported by Aslan et al indicated that the unfolded part of DNA can bind to the positively charged portion of BSA (Bovine Serum Albumin). Therefore, the mechanical stability, toxicity, and function of our origami device in cells require additional related assays.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, proteins may have a relatively weak interaction with our origami device because there is seldom empty space available for protein filling. For example, the study reported by Aslan et al indicated that the unfolded part of DNA can bind to the positively charged portion of BSA (Bovine Serum Albumin). Therefore, the mechanical stability, toxicity, and function of our origami device in cells require additional related assays.…”
Section: Resultsmentioning
confidence: 99%
“…DNA origami nanostructures are also increasingly employed in various materials science applications. Many studies have used DNA origami nanostructures as templates or lithography masks in order to transfer their shapes into other biological [ 22 , [91] , [92] , [93] ], organic [ [94] , [95] , [96] , [97] ], and especially inorganic materials [ 21 , 23 , 29 , 30 , [98] , [99] , [100] , [101] ]. Even if this requires conditions that deviate from the usual solution conditions, the shapes of the DNA origami templates are often transferred in a single processing step, so that their structural stability is usually of little concern.…”
Section: Materials Science Applicationsmentioning
confidence: 99%
“…The production of functional crystalline frameworks is arguably the ultimate goal of DNA nanotechnology, and surely one of its most applicable outcomes. 1,2 Methodologies have been developed to create a variety of DNA-based arrays with high spatial resolution in 1D [3][4][5][6] and 2D, [6][7][8][9][10][11][12][13][14][15][16] and a number of routes exists to extend geometrical control to the third dimension. 6,[15][16][17][18][19][20] None of the available approaches, however, has been able provide a general route for the preparation of 3D DNA frameworks that combine high porosity, embedded functionality, robustness to design changes, and the ability to retain local order over large lengthscales.…”
Section: Introductionmentioning
confidence: 99%